KONSEPFAIR VALUE DAN PENGARUHNYA TERHADAP RELEVANSI : SEBUAH TINJAUAN TEORITIS ATAS PENERAPAN IFRS - Agil Novriansa; Ahmad Subeki (AKUNTABILITAS, 2014)
Historical cost is currently perceived as less suitable to the current business development because it does not reflect the real value. Fair value comes to overcome the weaknesses of historical cost. In order to achieve the harmonization of international accounting standards, the International Accounting Standards Board (IASB) developed International Accounting Reporting Standards (IFRS) with the concept of fair value. Some countries have begun to adopt IFRS as their accounting standard. One of the controversial issues in the implementation of IFRS is its relevance in fair value. This paper will review the concept of fair value and its impact on relevance. This article uses literature study method. The result of theoretical review in this paper is fair value in financial statements of the company more reflect the actual value or condition of the earnings company when its reporting so that investors and creditors can predict future results or confirm and improve the previous expectations based on actual company conditions. This makes the accounting information of company relevant to support decision-making by investors and creditors. Several previous studies have also shown that fair value is relevant in helping investors to make decisions. This paper expand the literature on theoretical studies of fair value in the context of IFRS implementation.